Implementation Of An Electronic Voting System (E-Voting) In Village Head Elections In Maburai Village, Tabalong District, South Kalimantan Province - Aswin Samad; Mahyuni; M. Riduansyah Syafari (Wadah Inovasi Indonesia, 2022)
The purpose of this study was to determine the implementation of the electronic voting system in village head elections in Maburai Village, Murung Pudak District, Tabalong Regency, and to determine the factors that hindered the implementation of the electronic voting system in village head elections in Maburai Village, Murung Pudak District, Tabalong Regency, South Kalimantan. , Indonesia. This study uses in-depth qualitative research methods. The location of this research is at the Community and Village Empowerment Service of Tabalong Regency, which is the focus of this research is How is the Implementation of the Electronic Voting System in the Village Head Election in Maburai Village, Murung Pudak District and what are the factors that hinder the Implementation of the Electronic Voting System in the Head Election Village in Maburai Village, Murung Pudak District. Based on the results of the research and discussion analysis that has been described related to the Implementation of the Electronic Voting (E-Voting) System in the Election of Village Heads in Maburai Village, Murung Pudak District, Tabalong Regency, it has been successfully implemented properly, where the implementation of e-voting in village head elections has fulfilled the principles in the implementation of e-voting namely eligibility and authentication, uniqueness, accuracy, integrity, reliability, confidentiality, flexibility, convenience, certification, and transparency, even though the indicators of cost-effectiveness have not been met but this does not affect the effective quality of the e-voting system. The inhibiting factors in the implementation of the e-voting system in the election of village heads in Maburai Village were the lack of socialization carried out by the election committee so that many people did not know at all what e-voting was and how to use it and their was intervention from parties who wanted to hinder or thwart the implementation of the system, e-voting in village head elections because it is considered that the results can be manipulated.